Variable Renewable Energy Competitive Bidding Study - World Bank (Washington, DC: World Bank, 2022)
This study was commissioned to support the government of Pakistan, the provincial energy departments, and the electricity regulator in the implementation of competitive bidding for the procurement and development of all future variable renewable energy (VRE) capacity in the country. The decision was taken in 2017 to move from a “cost-plus” tariff-setting regime for future solar and wind power capacity to one based on the principles of competitive bidding, following international trends and the very positive results seen in terms of steep cost reductions in other countries. In many locations, these cost reductions have led to solar and wind becoming the “least-cost” form of power generation, although this has already been achieved in Pakistan through gradual declines in the tariff awarded on a cost-plus basis to solar and wind projects by NEPRA, the electricity regulator. The report is structured as follows: Section 2 outlines key background issues of relevance to competitive bidding mechanisms for RE in Pakistan; Section considers potential arrangements for deployment of competitive bidding; Section 4 analyzes tender governance processes; Section 5 examines detailed arrangements for the design of competitive bidding; Section 6 evaluates implementation arrangements; Section 7 considers the impact of the forthcoming Competitive Trading Bilateral Contract Market (CTBCM) on renewable energy (RE) competitive bidding mechanisms; Section 8 reviews information technology needs; Section 9 considers communications and marketing strategies; and Section 10 reviews the potential for introducing local content arrangements.